1992
DOI: 10.1111/j.1365-2249.1992.tb06479.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for transfer of cellular and humoral immunity to cytomegalovirus from donor to recipient in allogeneic bone marrow transplantation

Abstract: SUMMARYIn order to study the importance ofthe immune status ofthe donor in the development of immunity after allogeneic bone marrow transplantation (BMT), we monitored 23 cytomegalovirus (CMV) antibody-positive BMT recipients for humoral and cellular immunity to CMV, of whom 12 had a CMV antibody-positive and 11 a CMV antibody-negative marrow donor. Lymphocyte proliferation to CMV recovered significantly earlier after BMT in recipients of marrow from a CMV+ donor (10-4 weeks after BMT) compared with the recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 17 publications
0
8
0
5
Order By: Relevance
“…This suggests the possibility that the process of T‐cell depletion used at the center might have reduced the effective dose of CMV that recipients were exposed to. Thus, the donor may transmit CMV and/or immunity to the recipient under particular circumstances . Other risk factors for CMV infection include use of unrelated donors, high‐dose steroids, and GvHD .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the possibility that the process of T‐cell depletion used at the center might have reduced the effective dose of CMV that recipients were exposed to. Thus, the donor may transmit CMV and/or immunity to the recipient under particular circumstances . Other risk factors for CMV infection include use of unrelated donors, high‐dose steroids, and GvHD .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the reconstitution of CMV-specific T cell immunity by adoptive T cell transfer has been proposed for the treatment of chemotherapy-refractory CMV disease (11), and several clinical studies have shown its efficacy in patients requiring minimal or no immunosuppression (11,23,24). Adoptive transfer of non-manipulated donor lymphocytes also proved beneficial for the management of CMV and Epstein-Barr virus infections yet is often associated with an aGvHD caused by the presence of excessive doses of alloreactive T cells (26,27). Minimizing the risk of an aGvHD achieved by the generation of CMV-specific T cell clones by repeated stimulation of donor lymphocytes with the respective antigen showed the full potential of adoptive transfer of CMV-specific T cells without concomitant aGvHD (11,28).…”
Section: Discussionmentioning
confidence: 99%
“…Active CMV infection after transplantation is controlled by CMV-specific CD4 + T helper (Th) and CD8 + cytotoxic T lymphocyte (CTL) responses (7, 8). There is evidence for the transfer of donor CMV-specific immunity with the graft, since CMV seropositive recipients of seropositive BM reconstitute CMV-specific T cell immunity earlier than recipients of seronegative BM (9, 10). Although greater numbers of T cells are transferred with PBSC grafts, CMV infects early and committed hematopoietic progenitors (11, 12), which may result in transmission of a greater virus load with PBSC products.…”
Section: Introductionmentioning
confidence: 99%